Topographical and Compositional Gradient Tubular Scaffold for Bone to Tendon Interface Regeneration - Eleonora Bianchi; Angela Faccendini; Elena Del Favero; Caterina Ricci; Laura Caliogna; Barbara Vigani; Francesco Claudio Pavesi; Cesare Perotti; Rui M. A. Domingues; Manuela E. Gomes; Silvia Rossi; Giuseppina Sandri (MDPI AG, 2022)
The enthesis is an extremely specific region, localized at the tendon-bone interface (TBI) and made of a hybrid connection of fibrocartilage with minerals. The direct type of enthesis tissue is commonly subjected to full laceration, due to the stiffness gradient between the soft tissues and hard bone, and this often reoccurs after surgical reconstruction. For this purpose, the present work aimed to design and develop a tubular scaffold based on pullulan (PU) and chitosan (CH) and intended to enhance enthesis repair. The scaffold was designed with a topographical gradient of nanofibers, from random to aligned, and hydroxyapatite (HAP) nanoparticles along the tubular length. In particular, one part of the tubular scaffold was characterized by a structure similar to bone hard tissue, with a random mineralized fiber arrangement; while the other part was characterized by aligned fibers, without HAP doping. The tubular shape of the scaffold was also designed to be extemporarily loaded with chondroitin sulfate (CS), a glycosaminoglycan effective in wound healing, before the surgery. Micro CT analysis revealed that the scaffold was characterized by a continuous gradient, without interruptions from one end to the other. The gradient of the fiber arrangement was observed using SEM analysis, and it was still possible to observe the gradient when the scaffold had been hydrated for 6 days. In vitro studies demonstrated that human adipose stem cells (hASC) were able to grow and differentiate onto the scaffold, expressing the typical ECM production for tendon in the aligned zone, or bone tissue in the random mineralized part. CS resulted in a synergistic effect, favoring cell adhesion/proliferation on the scaffold surface. These results suggest that this tubular scaffold loaded with CS could be a powerful tool to support enthesis repair upon surgery.